THE IMPLEMENTATION OF NURSING FAMILY TO IMPROVE SELF CARE BEHAVIOUR OF PULMONARY TUBERCOLOSIS PATIENTS IN BIMA, WEST NUSA TENGGARA - Muhtar Muhtar; Abdul Haris (Jurnal Kesehatan Prima, 2016)
Abstract:  Tuberculosis is a public health problem entire world and becomes the third largest cause of death after cardiovascular and respiratory ailments, and the first largest infection diseases catagory. This research is intented to improve self-care behavior of pulmonary tuberculosis patients through the implementation of family nursing care. Methods: the method used in this study was randomized control group and pretest posttest design, this research involved two groups of subjects, namely the experimental group and the control group which were randomly determined. The population in this research were families with pulmonary tuberculosis patients which were registered and were undergoing tubercolosis treatment program in Bima, a number of respondents were 40 people who were divided into a control group and the experimental group. The sample used in this study was cluster random sampling technique. Moreover, analysis data was statistical test of Wilcoxon signed rank to examine the pre-post’s differences within the group and the Mann-Whitney test to examine the significance of differences between groups in significance level α ≤ 0.05. Results: Statistical tests Wilcoxon signed rank test indicated the difference of pre-post self-care demand (p = 0.000) and self-care agency (p = 0.000) in the treatment group, whereas there was no significant difference in the control group. There were differences in self care and self-care demand angency between groups at post test results (p = 0.000), whereas in the pre-test results there were no differences between the groups (p = 0.570 and p = 0.225). Conclusion: the application of family nursing care effectives in improving self-care behavior of patients with pulmonary  tuberculosis  through the increasing of patients’ conciousness of the need self-care demand as well as improving the ability of pulmonary tuberculosis patients in self-care agency.